IUESD - Integrated university education system for disabled : workshops 2000 proceedings - Šimšík, Dušan (Technical University, 2000)
Proceedings from a workshop that focused on the education system for disabled students in Europe. Intended for professional public.
Keywords: pedagogika; Persons with Disabilities; Education, Graduate; Evropa; Europe; studenti; Mainstreaming, Education; zdravotně postižení; studium vysokoškolské; postižení; integrovaná výuka; Students